Efisiensi Penggunaan Tempat Tidur di Ruang Rawat Inap: Studi Kasus Rumah Sakit Santa Elisabeth Medan - Pomarida Simbolon; Arjuna Ginting; Jev Boris; Adrian Martin Hutauruk; Anthonyus Anthonyus (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
One of the indicators that must be considered by hospitals to improve hospital services is the efficiency of inpatient services, especially in the use of beds. In monitoring the efficiency level of bed use in the treatment room, it can be seen from the Barber Johnson chart based on the calculation results of Bed Occupancy Ratio (BOR), Average Length Of Stay (AvLOS), Internal Turn Over (TOI), Bed Turn Over (BTO). Santa Elisabeth Hospital Medan has 250 beds in inpatient rooms and 696 patients in September 2021. The purpose of this study was to determine the efficiency of bed use in inpatient rooms based on Barber Johnson charts. This type of research is descriptive. The subject of the study was the daily inpatient census recapitulation at the Santa Elisabeth Hospital Medan in September 2021. The informant was one medical record officer in the reporting section. The study was conducted in November 2021. Data collection used observation techniques. The results showed that the calculation of BOR in September 2021 was 42.20%, LOS was 5.69 days, TOI was 7.27 days and BTO was 2.34 times. The values ​​of LOS BOR, TOI and BTO are not ideal because they do not meet the standards due to the small number of patients. It is recommended to the medical record officer at Santa Elisabeth Hospital Medan to pay attention to the formula used in calculating the BOR, AvLOS, TOI and BTO values ​​and to make a Barber Johnson chart regularly every year so as to increase the efficiency and effectiveness of the use of beds in the inpatient room and as a planning strategy for the following year.